ANALISIS PENGARUH PERCEIVED QUALITY, PERCEIVED VALUE, DAN PERCEIVED RISK TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Ayu Puspitasari, Dyah; Indriani, Farida (Diponegoro Journal of Management, 2018)
Online shopping sites appear as alternative choices for buyers. Lazada is the most popular  online  shopping  site  in  Indonesia  which  has  an  official  website  named lazada.co.id. In 2018 Lazada have decrease in the number of visitors which caused a decrease buying interest in Lazada. on the other hand began, many online shops appear that not have official sites and only rely on promotion and sales through social media only. This has an impact on the emergence of alternative purchasing decisions from consumers will buy the product.will buy the product.This research aims to analyze the influence of perceived quality, perceived value, and perceived risk towards the customer’s online purchase decision of official website Lazada  and  social  media  online  shop  EolKPop.  The  sampling  method  used  on  this research is non-probability sampling with purposive sampling technique. Samples were collected  from  100  respondents  on  Semarang  who  had  made  an  online  purchase transaction at official web lazada.co.id and 100 respondents who have made an online purchase transaction in social media online shop Eolkpop. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression test, t-test, f-test, determination test and independent t test.The result showed that perceived quality and perceived value has positive and significant influence towards the online purchase decision on official website Lazada and social media online shop EolKPop while perceived risk has negative not significant influence towards the online purchase decision on official website Lazada and  social media online shop EolKPop.